Process Evaluation of the Universal Immunization Program in Imphal-East District of Manipur: A Cross-Sectional Study - Dayananda Ingudam; Heisnam Kulabidhu Singh; Longjam Usharani Devi (Wolters Kluwer Medknow Publications, 2022)
Background: Various strategies have been made to make vaccines universally available including to most hard-to-reach and vulnerable population. However, change in coverage level never reached upto expected level in spite of giving so much effort by the Govt. of India and World bodies. Therefore, there is the need to look beyond. Hence, the process evaluation of Universal Immunization Program (UIP) was conducted to evaluate the process of UIP using selected variables. Methods: A cross-sectional observation was done during the period from May 2017 to April 2020 among the 14 health-care facilities and 36 selected session sites, and interview was done to 48 health-care providers working at different levels, located in Imphal East district of Manipur. Both checklist and pretested semi-structured questioners were used for collection of data. Descriptive statistics such as frequency, proportion, and percentage were used. Results: Ice-lined refrigerator and Deep-freezer were found to be present in working condition in 11 (100%) centers. The use of vaccine carrier was found in all 36 (100%) centers. Way of vaccine administration was found to be correct in 26 (72.2%) centers. Availability of up-to-date microplan was found in 18 (78.3%) centers. Conclusions: Barriers in the UIP were not uniform throughout the villages and districts. Hence, area-specific measures need to be taken up for overcoming the barriers and challenges.